Analisis Jaringan Distribusi Air Bersih Menggunakan Software Epanet 2.0 Pada Perumahan Graha Cemerlang - Trivana Illa; Mary Selintung; Hanna Mariani Singgih (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Clean water is the main resource for human needs of good quality for consumption or use in daily activities, including efforts to empower, maintain and protect cleanliness. PDAM Kota Maros is demanded to be able to meet the water needs that are used by living things and the environment. Human needs will increase from time to time due to the increasing number of people needing this water. One way to meet the demand for water is to develop pipelines. In carrying out the analysis of clean water distribution piping networks, tools are needed to make it easier to carry out the analysis, such as the Epanet 2.0 program. The EPANET application is a computer program that provides hydraulic simulations and trends in the quality of water flowing through pipes. This software can model the design of a water distribution network using reservoirs, pumps, valves and connecting lines as symbols of the pipes used. EPANET 2.0 can determine the amount of pressure, flow velocity, and flow rate. In this writing, Graha Cemerlang Housing is used as the object of research on clean water accessible to the people living in Graha Cemerlang Housing. Knowing the need for clean water in Graha Cemerlang Housing in 2021 and knowing that the clean water pipeline network in Graha Cemerlang Housing has been able to serve Graha Cemerlang Housing with the number of houses that subscribe to Graha Cemerlang Housing, namely 330 units having a total requirement of 6.009 l/s and the results of network analysis clean water pipes produce a residual pressure value that meets the hydraulic criteria in 2021.